A green construction method of a double-crosslinked porous membrane and a method for separating / enriching uranium therefrom

By constructing a double crosslinked porous membrane, using phytic acid modified nano-concave-concave-concave-corrosive rock stone, sodium alginate and polyvinyl alcohol, the selectivity and cost problems of uranium separation/enrichment in water bodies are solved, and efficient and low-cost uranium separation and enrichment effects are achieved.

CN119455917BActive Publication Date: 2025-04-29NORTHWEST INST OF ECO ENVIRONMENT & RESOURCES CAS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411744848.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-29
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art has problems such as low selectivity, high preparation cost, difficulty in recycling and environmental pollution in the efficient separation/enrichment of uranium in water bodies. In particular, sodium alginate microspheres have shortcomings such as uneven cross-linking and limited pore structure in uranium separation applications.

Method used

By using phytic acid modified nano-concave-concave-concave-corrosive rock, sodium alginate and polyvinyl alcohol as the main raw materials, combined with foam template method, cast film formation and dual crosslinking technology, a double crosslinking porous membrane with a dual crosslinking porous structure, excellent adsorption performance, acid and alkali resistance and high stability were constructed.

Benefits of technology

It has achieved low-cost and efficient separation and enrichment of uranium in water bodies, with good application prospects and environmental friendliness, and can effectively treat high-concentration uranium-containing wastewater and nuclear accident wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455917B_ABST
    Figure CN119455917B_ABST
Patent Text Reader

Abstract

The present invention discloses a green construction of a double cross-linked porous membrane and a method for separating / enriching uranium therefrom. First, a phytic acid-modified attapulgite suspension, polyvinyl alcohol and a sodium alginate / glycerol mixed aqueous solution are mixed in proportion, and a water-based foam film-forming liquid is obtained by high-speed stirring, and then a double cross-linked porous membrane is obtained by tape casting and calcium ion cross-linking, and applied to the separation / enrichment of uranium in water. The present invention preferably uses phytic acid-modified nano-attapulgite, sodium alginate and polyvinyl alcohol as main raw materials, and constructs a double cross-linked porous membrane with a semi-interpenetrating network porous structure, excellent adsorption performance, acid and alkali resistance and high stability through green combination processes such as foam template method, tape casting and double cross-linking, which can realize the separation and enrichment of uranium in water at low cost and high efficiency, and can also be applied to specific situations such as high-concentration uranium-containing wastewater and nuclear accident wastewater treatment by means of step-by-step adsorption and multi-step separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for constructing a double-crosslinked porous membrane and applying it to uranium separation / enrichment, and in particular to a green construction of a attapulgite / sodium alginate / polyvinyl alcohol double-crosslinked porous membrane and a method for applying it to uranium separation / enrichment in water. Background Art

[0002] With the rapid development of industry and the rapid growth of population, traditional energy is no longer sufficient to meet the needs of development, and people are paying more attention to and attaching importance to the development and utilization of clean energy. Nuclear energy, as an emerging, clean, efficient and sustainable energy, has the characteristics of high energy density, low carbon emissions (near zero emissions), and low operating costs. It is considered to be a key component of future low-carbon energy and also occupies an indispensable and important position in the construction of my country's green and low-carbon energy system. As the "cornerstone of strong nuclear power and the granary of nuclear power", the development and safe supply of uranium (U) are crucial to the long-term sustainable development of nuclear energy. However, with large-scale uranium mining / enrichment, uranium product processing, unreasonable nuclear waste emissions and nuclear accidents, a large amount of uranium-containing wastewater is inevitably released into the ecological environment. In the aquatic ecological environment, uranium is mainly in the form of highly soluble uranyl (UO2 2+ ) is a high-risk pollutant in the environment. It will migrate and spread to the biosphere with surface runoff and underground seepage, and transfer through the food chain to endanger the ecological environment and human health. In addition, the chemical toxicity and radioactivity of uranium can cause irreversible kidney damage, urinary system diseases, DNA damage and destruction of biological molecules. Therefore, once uranium-containing wastewater is discharged into the environment, it will cause serious harm to the entire ecosystem. Research on efficient separation / enrichment methods of uranium in water bodies is of great strategic significance to water resource protection, human safety, uranium product processing, and ensuring the sustainable development of nuclear energy.

[0003] So far, the methods for efficient separation / enrichment of uranium in water reported in research mainly include traditional adsorption, ion exchange, extraction, membrane separation, chemical reduction and new electrochemical reduction, photocatalysis, friction catalysis, etc. These methods show application potential. Among them, adsorption is the most widely used method for uranium separation / enrichment in water. It has the advantages of simple operation, high efficiency and low cost. The key lies in the development of adsorbents with high adsorption capacity, rapid adsorption, low cost and stable performance. However, the selectivity of a single adsorbent for uranium is not high and the adsorption effect is not ideal, while the composite adsorbent has the defects of high preparation cost, difficult recovery, instability and potential environmental pollution. Therefore, it is crucial to construct an adsorbent with high adsorption performance and environmental friendliness in a green and economical way for the separation / enrichment of uranium in water.

[0004] Essentially, efficient separation / enrichment of uranium from water requires high-performance (high affinity, high selectivity, high stability) and low-cost adsorption materials, which requires comprehensive design from multiple aspects such as front-end raw material optimization, mid-end preparation principle and process optimization, and back-end application. Palygorskite (PAL) is a 2:1 type layered chain structured hydrated magnesium-aluminum silicate clay mineral with a nanorod-like crystal morphology, regular pore structure, and surface active silanols. It is widely available, green and environmentally friendly, and low-cost. The unique crystal structure and physical and chemical properties of attapulgite give it excellent adsorption, carrier, colloid and toughening and reinforcement properties. Through further nano-sizing or modification, the surface adsorption active sites and pore structure can also be increased. Sodium alginate (SA) is a polysaccharide biopolymer extracted from kelp, which has the characteristics of easy degradation, biocompatibility and excellent film-forming properties. In addition, its molecular chain contains a large number of -COOH and -OH functional groups, which can be used as adsorption and coordination groups. Polyvinyl alcohol (PVA) is a biodegradable, safe and cheap water-soluble polymer with good film-forming properties and biocompatibility. It can be used as an adhesive, emulsifier, dispersant, etc. Its hydrogel has been used in ophthalmology, wound dressings, artificial joints, pharmaceutical membranes, and artificial kidney membranes. Therefore, constructing functional composite adsorption materials with attapulgite, sodium alginate and polyvinyl alcohol is expected to achieve efficient separation and enrichment of uranium in water.

[0005] Chinese invention patent CN115837268A discloses a modified attapulgite reinforced sodium alginate hydrogel, which selectively absorbs phytic acid in water; CN114558558A discloses a sodium alginate and polyvinyl alcohol double cross-linked gel microsphere doped with attapulgite, which absorbs Cd, Pb, Cu and other ions in water; CN114632501A discloses a composite cross-linked microsphere obtained by reacting polyvinyl alcohol, sodium alginate, sodium carboxymethyl cellulose and attapulgite, which is used to treat dyes (methylene blue) or heavy metal ions (Cd, Pb ions) in wastewater; CN10 5013450B discloses a bimetallic sodium alginate / carboxymethyl cellulose bifunctional microsphere, which can adsorb anions such as fluoride ions and cations such as uranyl ions; CN116532093A discloses a hydrogel prepared with montmorillonite, agar and sodium alginate, which is used for the treatment of low-concentration uranium-containing wastewater; CN108940225B discloses a sodium alginate / amino mesoporous silica gel ball, which is used for the treatment of low-concentration uranium-containing wastewater; CN104941592A discloses a genetically recombinant brewer's yeast / sodium alginate magnetic biocomposite microsphere, which is used for the adsorption of uranium in aqueous solution.

[0006] Although some research has been conducted on the separation / enrichment of uranium using sodium alginate-based composite microspheres, the preparation process of sodium alginate microspheres is relatively complicated, the particle size of the prepared microspheres is mostly 3-6 mm, and the calcium ion concentration used for cross-linking is relatively high, requiring multiple washing and freeze-drying, vacuum drying and other post-processing steps. At the moment when calcium ions are cross-linked to form adsorbent microspheres, the cross-linking rate and degree of the outer surface of the microspheres are much higher than those inside, and a large number of adsorption functional groups such as hydroxyl and carboxyl groups inside are not effectively utilized. Even the outer layer with high cross-linking density will limit or prevent large-radius ions and water molecules from entering the microspheres, resulting in the need to improve the separation efficiency and rate of sodium alginate microspheres for some elements with large ionic radii (such as uranium). At the same time, if the same volume of film-forming liquid is used to prepare microspheres and films, the total surface area of ​​the microspheres can only be greater than the surface area of ​​the membrane when the radius of the microspheres is small enough (<0.113 cm), and the preparation process difficulty and cost of microspheres with extremely small particle sizes are higher than those of the cast film method. Therefore, compared with microsphere adsorbents, film adsorbents have the advantages of large specific surface area and simple and efficient preparation process.

[0007] From the perspective of material space tectonics, the construction of high-performance adsorbent materials based on function-oriented design principles has attracted much attention, and green methods and process combinations such as foam template method, double cross-linked porous network and plant synergy have also played an important role in the construction and application of high-performance adsorbent materials. On this basis, the present invention systematically analyzes the efficient separation / enrichment method of uranium in water and the application of sodium alginate-based adsorption microspheres in water uranium separation technology, and uses phytic acid-modified nano-attapulgite as a stabilizer, polyvinyl alcohol and sodium alginate / glycerol mixed aqueous solution as a continuous phase, and constructs a double cross-linked porous membrane through a combination of green water-based foam template method and calcium ion cross-linking, and further applies the double cross-linked porous membrane to the separation / enrichment behavior of uranium in water. A comprehensive analysis and evaluation are carried out, providing a method for separating / enriching uranium using a double cross-linked porous membrane. This technology or process can be used as a green functional composite membrane material to solve the problem of efficient separation / enrichment of uranium in water and one of the potential ways to safely treat uranium-containing wastewater. Moreover, there are no relevant research reports on this technology, and there is no precedent for its application. Summary of the invention

[0008] In view of the serious ecological and environmental hazards caused by the above-mentioned uranium-containing wastewater, the difficulties in efficient separation / enrichment of uranium in water bodies, and the shortcomings of sodium alginate gel microspheres in uranium separation applications, the present invention, based on a full understanding of the efficient separation / enrichment method of uranium in water bodies and the foam template method for constructing porous adsorption materials, uses phytic acid-modified nano-attapulgite, sodium alginate and polyvinyl alcohol as main raw materials, and through green combination processes such as foam template method, cast film forming and double cross-linking, constructs a double-cross-linked porous membrane with a double-cross-linked porous structure, excellent adsorption performance, acid and alkali resistance and high stability. The separation and enrichment of uranium in water bodies can be achieved at low cost and high efficiency, and can also be applied to specific situations such as high-concentration uranium-containing wastewater and nuclear accident wastewater treatment by means of step-by-step adsorption and multi-step separation.

[0009] The green construction method of the double-crosslinked porous membrane of the present invention is characterized by comprising the following steps:

[0010] (1) The nano-attapulgite obtained by rod crystal bundle dissociation treatment is uniformly dispersed in water to obtain a uniform suspension with a solid content of 7%, phytic acid of 25-35% of the mass of attapulgite is added to the suspension, and the suspension is ultrasonically treated for 10-20 minutes to obtain a uniform phytic acid-modified attapulgite suspension.

[0011] The nano-attapulgite is obtained by crushing the natural attapulgite ore, slurrying and hydrating for 6 hours, and cyclone classification, and then ultrasonic or high-pressure homogenization and strong drying to obtain nano powder. The crushing is to crush the attapulgite to 50-100 meshes. In the preparation process of the nano-attapulgite powder, the ultrasonic treatment is carried out at a frequency of 20-40kHz and a power density of 100-300W / L for 5-10min; the high-pressure homogenization is carried out at a pressure of 30-50MPa. The temperature of the strong drying treatment is 90-110℃, and the classification frequency is 5-15Hz. The attapulgite content in the nano powder is ≥70%, and the rod crystal length is ≥0.9μm.

[0012] In the process of modifying nano-attapulgite with phytic acid, ultrasonic treatment is carried out by using a cell disruptor at room temperature and a power of 200 to 500W.

[0013] The particle size, dispersibility, specific surface area and colloidal properties of solid particles are the key factors affecting the formation and stability of Pickering foam. Nanoparticles have a large diffusion coefficient, specific surface area and dispersibility. They can be quickly adsorbed and densely arranged on the foam surface at a low addition amount to form a dense mechanical barrier film, which effectively prevents the collision and aggregation between bubbles and increases the mutual repulsion between bubbles, effectively improving the stability of the foam structure. From Table 1 and Figure 1It can be seen that under the strong cavitation, shear, collision and temperature effects brought by low-frequency high-power ultrasound or high-pressure homogenization, the dispersibility of the rod crystals of attapulgite is significantly improved, and a large number of rod crystal aggregates have been non-destructively and efficiently dissociated into nano-attapulgite ( Figure 1 b), and the average length and aspect ratio of the nanorods did not change significantly after the rod bundle dissociated ( Figure 1 d), the length of the rod crystal changes in a normal distribution and the average length is ≥ 0.9 μm. 50 Reduced to about 1 / 3 of the original; with a larger specific surface area (increased from 186.20 to 213.85 or 236.05m 2 / g), a large number of highly dispersed rod crystals are irregularly arranged to form a large number of stacked pores (the total pore volume also increases from 0.31 to 0.36 or 0.38 cm 3 / g), which is beneficial to the subsequent phytic acid modification and compounding; the initial and 10min shear rotational viscosity of nano-attapulgite are much higher than those before dissociation, and the better suspension stability and colloidal properties are beneficial to improving the long-term stability of Pickering foam. The attapulgite with a large length / diameter ratio has better viscosity-increasing and stabilizing effects on the water-based foam system after the dissociation of the rod crystal bundle.

[0014] Table 1 Changes in the physical and chemical properties of attapulgite before and after dissociation of rod crystal bundles

[0015]

[0016] Phytic acid (PA) is a saturated cyclic acid with 6 phosphate groups, non-toxic, biocompatible, and environmentally friendly. It is widely found in plants such as beans, cereals, dried fruits, vegetables, and fruits. It can be extracted from plants and is edible. In the present invention, phytic acid is preferably used as a modifier of attapulgite, mainly for the following two considerations: on the one hand, phytic acid, as a mineral chelating agent, can be combined with nano-attapulgite to further improve the colloidal properties of attapulgite suspensions, and by increasing the steric hindrance and contact distance between nano-rod crystals, it is not only conducive to the dispersion of nano-attapulgite rod crystals, but also effectively inhibits the re-aggregation of dispersed nano-rod crystals, forming a suspension with high suspension stability and high viscosity; on the other hand, the unique structure of phytic acid ring molecules containing 6 phosphate groups and 12 free hydrogens determines the super strong chelating performance, and it has strong binding ability with uranyl ions and high selectivity. In the construction process of double cross-linked porous membranes, the introduction of phytic acid can also improve the adsorption amount and selectivity. However, excessive addition of phytic acid will reduce the viscosity of the attapulgite suspension and the film-forming liquid, weaken the film-forming performance of the double-cross-linked porous membrane, and significantly increase the cost of membrane preparation. After multiple experimental verifications and comprehensive considerations, the preferred amount of phytic acid added is 35-50% of the mass of attapulgite, and the mass fraction of phytic acid in the final membrane material is about 0.5%. In addition, after mixing nano-attapulgite with phytic acid, cell disruption treatment at high power is beneficial to phytic acid modification, and its cavitation effect will improve the modification efficiency and rate. The obtained phytic acid-modified attapulgite suspension still shows no sedimentation or flocculation after standing for 7 days, showing excellent suspension stability and colloidal properties.

[0017] (2) The phytic acid modified attapulgite suspension, polyvinyl alcohol aqueous solution (polyvinyl alcohol mass fraction is 4%) and sodium alginate / glycerol mixed aqueous solution (sodium alginate and glycerol mass fractions are 2.0% and 0.4%, respectively) are mixed in a volume ratio of 10-15:10-15:70-75, and stirred at 6000-8000 rpm for 10-20 min to obtain a uniform film-forming liquid.

[0018] The sodium alginate is a powder with a 10g / L solution viscosity of ≥0.02Pa.S at 20°C; the polyvinyl alcohol is a solid particle with an alcoholysis degree of 87-89% and a viscosity of 20.5-24.5CP.

[0019] Preferably, the peel or seed shell of a saponin-rich plant is washed with water, dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain plant powder, and the plant powder is added to a mixed solution of phytic acid-modified attapulgite, polyvinyl alcohol, and sodium alginate / glycerol, and stirred at 6000 rpm for 20 minutes to form a uniform film-forming liquid. The saponin-rich plant is at least one of angelica, soapberry, or saponin; the amount of the plant powder added is 0.25-0.50% of the mass of the mixed solution of phytic acid-modified attapulgite, polyvinyl alcohol, and sodium alginate / glycerol.

[0020] The present invention disperses the phytic acid modified attapulgite slurry at high speed in a mixed aqueous solution of polyvinyl alcohol and sodium alginate / glycerol, and the phytic acid modified attapulgite nanorod crystals are evenly distributed and adsorbed on the air-water interface to produce foam with excellent stability, and further optimizes key parameters such as the addition amount, stirring speed, and time to obtain a film-forming liquid with a uniform and stable foam structure. From the optical microscope photo ( Figure 2 ) It can be seen that the film-forming liquid is composed of a large number of circular bubbles of similar size and uniform dispersion and viscoelastic liquid. The high-viscosity modified attapulgite suspension effectively prevents the coarsening and agglomeration of bubbles, and the viscosity and fluidity of the foam film-forming liquid after optimizing the preparation conditions meet the conditions for casting film formation, which is conducive to smooth flow and extension of film formation. In the prepared film-forming liquid, nano-attapulgite with a large length / diameter ratio can form a three-dimensional network structure through hydrogen bonds and van der Waals forces, and the modifier phytic acid can react with polyvinyl alcohol to form a phosphate structure, and produce strong intermolecular interactions through hydrogen bonds, causing phytic acid-modified attapulgite and polyvinyl alcohol to form a cross-linked network structure in the bubble gap and continuous phase, providing a protective barrier for the bubbles, inhibiting the flow of bubbles and liquid, and increasing the bubble stability and liquid film strength.

[0021] Through the water-based foam template method, the cross-linked network structure formed by attapulgite, phytic acid and PVA and the microbubbles sealed in the high-viscosity phase during stirring will keep the continuous phase in a stable porous structure. At the same time, active uranium-absorbing functional groups such as carboxyl, hydroxyl, and phosphoric acid will be evenly distributed on the surface of the stable bubbles and in the porous continuous phase, which is conducive to improving the efficiency and rate of subsequent reactions with uranium. Furthermore, the active ingredients in saponin-rich plants and phytic acid-modified attapulgite are selected as combined stabilizers for aqueous foams. The plant active ingredients and nano-attapulgite are used to synergistically stabilize the aqueous foam, which is not only conducive to obtaining a film-forming liquid with a stable and uniform foam structure, but also can reduce the amount of nano-attapulgite added, which is conducive to the high-value utilization of non-renewable clay minerals.

[0022] (3) Casting the above-mentioned film-forming liquid into a film and controlling the film thickness to be 0.75-1.25 mm, and adding a water-soluble calcium salt solution with a mass fraction of 1.0-2.0% to completely immerse the film. After 4-8 hours, take out the above-mentioned film and wash it with deionized water for 3-5 times to obtain a double-crosslinked porous membrane.

[0023] The water-soluble calcium salt is at least one of calcium chloride, calcium iodide, calcium dihydrogen phosphate or calcium nitrate. Preferably, the film washed with deionized water is vacuum dried at a vacuum degree of -0.08 MPa and 40-50° C. for 8-12 hours, or freeze-dried at -20° C. for 12-24 hours to obtain a double cross-linked porous membrane.

[0024] The present invention directly casts a uniform and stable foam film-forming liquid into a film, controls the film thickness to be 0.75-1.25 mm by controlling the mass of the film-forming liquid, and adds a water-soluble calcium salt solution to completely immerse the film. After secondary calcium ion cross-linking, the excess calcium ions are washed away. The double-crosslinked porous membrane ( Figure 3 ). In the preparation process of the double-crosslinked porous membrane, controlling the thickness of the liquid film is conducive to the full crosslinking of the film and calcium ions, retaining the original uniform bubbles and porous composite structure. At the same time, if the calcium ion concentration is too low, the washed film will be directly calcium crosslinked. If the crosslinking degree is insufficient, the mechanical strength and toughness of the film will be greatly reduced. If the calcium ion concentration is too high, a large number of active adsorption functional groups will be masked or coated, reducing the adsorption and separation efficiency of the film material. Therefore, in the process of secondary calcium crosslinking with wet membrane, calcium ion concentration is one of the key factors affecting film forming properties, membrane mechanical properties and adsorption efficiency. After experimental optimization, under the same conditions, after crosslinking with 1.0-2.0% water-soluble calcium salt solution, the double-crosslinked porous membrane has good strength and toughness and excellent adsorption and separation efficiency. When added to uranium-containing wastewater with a uranium concentration of 200ppm and a pH value of 5.9, the uranium adsorption amount and removal rate can reach 351mg / g and 92.22%. Preferably, the washed double-crosslinked porous membrane can be vacuum dried or freeze-dried, which helps to retain the bubbles on the surface of the membrane material and the internal pore structure, increases the total adsorption sites of the material, and facilitates storage and transportation.

[0025] from Figure 4 It can be seen that the pure sodium alginate membrane was completely dissolved within 3 minutes after being immersed in a neutral water environment, while the double-crosslinked porous membrane of the present invention was immersed in solutions with different pH values ​​(1, 5, 9, 13) and still maintained its original shape after 14 days of immersion, indicating that it has excellent acid and alkali resistance; in the batch adsorption experiment, it was also found that after 24 hours of shock reaction with the uranium-containing solution, the double-crosslinked porous membrane still maintained its original shape. From the thermogravimetric curve and the differential thermogravimetric curve ( Figure 5) It can be seen that the residual mass of pure sodium alginate membrane, calcium cross-linked membrane and double cross-linked porous membrane heated to 800℃ were 24.12%, 26.32% and 29.53% respectively; compared with pure sodium alginate membrane, the maximum weight loss peak of calcium cross-linked and double cross-linked porous membrane shifted to the high temperature region, and the maximum mass loss rate was -3.67% / ℃ and -1.82% / ℃ respectively, which was much lower than that of pure sodium alginate membrane (-10.16% / ℃), which shows that the double cross-linked porous structure of the membrane has excellent stability. From the TEM image of the double cross-linked porous membrane ( Figure 6 ) It can be seen that the double-crosslinked porous membrane is a semi-interpenetrating network porous structure under the microscope. In summary, the comprehensive optimization strategies such as double-crosslinked porous structure, rich uranium-absorbing functional groups, acid and alkali resistance and high stability, and spatial structure design and performance improvement have laid a foundation for the application of double-crosslinked porous membranes in the efficient separation / enrichment of uranium in water and the treatment of uranium-containing wastewater.

[0026] A double-crosslinked porous membrane constructed by any of the above methods.

[0027] The method for separating / enriching uranium with a double-crosslinked porous membrane as described above is characterized in that: the pH value of a uranium-containing water body with a U(VI) concentration of 2 to 200 ppm is adjusted to 5.0 to 7.0, 0.5 to 2.0 g / L of a double-crosslinked porous membrane is added thereto, and after shaking or stirring at room temperature for 60 to 240 minutes, the uranium concentration in the solution is measured, and the uranium separation efficiency is calculated according to the following formula:

[0028]

[0029] If the uranium separation efficiency is ≥95%, the double-crosslinked porous membrane is removed from the uranium-containing water body to achieve uranium separation / enrichment; if the uranium separation efficiency is less than 95%, the porous crosslinked membrane is removed and a new double-crosslinked porous membrane is added to the uranium-containing water body again, and the treatment is circulated until the uranium separation efficiency is ≥95%.

[0030] like Figure 7 (a, b) show the microscopic photos of the double cross-linked porous membrane prepared by the present invention before and after uranium adsorption. It can be clearly observed that the double cross-linked porous membrane prepared by the present invention contains abundant vesicle structures on the surface and inside, and the appearance is white ( Figure 3 ), while the double cross-linked porous membrane appears yellow after adsorption of uranium ( Figure 7b), indicating that a large amount of uranyl in the uranium-containing water was adsorbed or deposited on the surface of the film. The chromaticity values ​​of the film were tested by a colorimeter. Before adsorption, L*, a* and b* were 21.55±0.10, -0.67±0.05 and -1.86±0.08, respectively. After adsorption, the chromaticity values ​​of the film () were 35.03±1.15, -6.09±0.39 and 17.19±0.02, respectively. The yellow-blue color value b* value changed from negative to +17, confirming that the film turned yellow after uranium adsorption. The non-flat spatial structure such as the vesicle structure and uniform pores of the double-cross-linked porous membrane greatly increased the contact area and collision probability between the membrane and uranium, which is conducive to the rapid adsorption and efficient enrichment of yellow uranyl on the surface of the double-cross-linked porous membrane. From the FTIR spectra before and after uranium adsorption ( Figure 7 d) By comparison, it can be found that the FTIR spectrum of the adsorbed membrane material showed an obvious O=U=O characteristic peak (909.8cm -1 ), indicating that the uranyl ions are chemically bonded to the double-crosslinked porous membrane, and the stretching vibration peak of C=O is weakened and shifted (from 1620 to 1629 cm -1 ) confirmed the coordination reaction between carboxyl and uranyl ions. From the XPS spectra of the double-crosslinked porous membrane before and after uranium adsorption, it can be seen that the full spectrum of the membrane material after adsorption ( Figure 8 In a), obvious U characteristic peaks (U4f5, U4f7, U4d3, U4d5) appeared, indicating that uranium was adsorbed and deposited on the double-crosslinked porous membrane; high-resolution U4f spectrum ( Figure 8 b) shows that the binding energies are 392.8eV and 382.0eV respectively, indicating that the valence state of uranium is still +6, indicating that the adsorption process is mainly based on coordination reaction and does not involve reduction reaction; high-resolution C1s, Ca2p, P2p and O1s spectra ( Figure 8 cf) indicates a change in the electron cloud density, indicating that the interaction between the double-cross-linked porous membrane and uranium includes at least the coordination reaction between the carboxyl group in calcium alginate and uranium, the substitution reaction between uranium and calcium ions, and the complexation reaction between phosphate and uranium, and that the multiple reactions synergistically improve the adsorption and separation efficiency of uranium.

[0031] The present invention also systematically investigates the uranium separation / enrichment performance of the prepared double cross-linked porous membrane. The double cross-linked porous membrane is added to a water body with a uranium concentration of 2 to 200 ppm at a solid-liquid ratio of 0.5 g / L. The adsorption thermodynamic curve is as follows: Fig. 9 As shown in (a), with the increase of uranium concentration in uranium-containing water, the adsorption amount of uranium by the double-crosslinked porous membrane increases linearly, and it has excellent uranium adsorption and separation efficiency, especially in the high concentration area (100-200ppm), the adsorption amount can reach 361mg / g, and the removal rate is greater than 95%; the adsorption model fitting confirmed that the adsorption isotherm fits well with the Langmuir adsorption isotherm (R2 =0.99982), confirming that uranium was enriched on the double-crosslinked porous membrane in a monolayer adsorption mode. Fig. 9 (b) is the adsorption boundary curve. It can be seen that when the double-crosslinked porous membrane prepared by the present invention is added to uranium-containing water with a pH value of 5-7 and a uranium concentration of 200 ppm, it shows a relatively high adsorption amount (318-351 mg / g) and removal rate (84-92%). Fig. 9 (c) is the adsorption kinetic curve. The interaction between the double-crosslinked porous membrane and uranium belongs to a rapid adsorption process. The adsorption amount reaches 221 mg / g after 1 hour of contact, and the adsorption equilibrium is reached in about 4 hours. Without drying treatment, the spatial structure retention rate of the double-crosslinked porous membrane is higher, so that it has excellent uranium separation efficiency, and also avoids the water absorption and swelling process of the dry membrane entering the water body. Therefore, based on the unique double-crosslinked porous structure and rich adsorption functional groups of the double-crosslinked porous membrane prepared by the present invention, it has a high removal efficiency and adsorption rate for uranium in water bodies, which helps to apply it to high-value applications in the interception, separation and enrichment of uranium in uranium-containing water bodies. In addition, how to quickly and efficiently separate the adsorption saturated adsorbent from the liquid phase is also one of the specific application technical difficulties. After the adsorption equilibrium, the uranium separation efficiency in two cases, namely, taking the supernatant after removing the membrane from the water body after adsorption saturation and taking the supernatant after centrifugation, was compared and analyzed. From such as Fig. 9 (d) It can be seen that after experimental verification under various experimental conditions, whether or not solid-liquid separation is performed has almost no effect on the uranium adsorption and removal rate of the membrane material. This shows that uranium is firmly adsorbed on the double-cross-linked porous membrane through chemical bonds, and no uranium precipitation is generated during the process. It also promotes the application of double-cross-linked porous membranes in special scenarios such as high-concentration uranium-containing wastewater and nuclear accident wastewater treatment through step-by-step adsorption and multiple addition modes.

[0032] In summary, the present invention has the following advantages compared with the prior art:

[0033] 1. The present invention adds phytic acid-modified nano-attapulgite to a mixed solution of sodium alginate / glycerol and polyvinyl alcohol, utilizes attapulgite nano-rod crystals and a high-viscosity continuous phase to synergistically stabilize aqueous foam, and obtains a film-forming solution rich in Pickering foam and active adsorption functional groups. Then, through green combination processes such as cast film forming and calcium ion cross-linking, a double-cross-linked porous membrane with phytic acid-modified attapulgite & polyvinyl alcohol and sodium alginate & calcium ions as the main cross-linking system is constructed, which has a semi-interpenetrating network porous structure, excellent adsorption performance, acid and alkali resistance and high stability, and is beneficial to solving the ecological and environmental hazards caused by uranium-containing wastewater and the problems of efficient separation / enrichment of uranium in water bodies.

[0034] 2. The present invention starts from the perspective of material spatial tectonics and takes function-oriented design as the principle. It adopts green processes such as foam template method and ion cross-linking to efficiently incorporate the preferred active uranium-absorbing groups / complexing ligands (carboxyl, hydroxyl, phosphate, etc.) and replaceable ions (calcium, magnesium ions, etc.) into the microstructures such as vesicles and pores of the double-cross-linked porous membrane, and combines the thermodynamics, kinetics, pH boundary and other adsorption behavior evaluations of the system to make full use of the unique spatial structure of the film, the affinity of the active groups with uranium, and the synergistic effect of the membrane adsorption separation method, so as to achieve the separation and enrichment of uranium in water at low cost, high efficiency, rapid and stable, and has good application and promotion prospects.

[0035] 3. The film construction method of the present invention and its application in the method of uranium separation / enrichment effectively utilizes the combined processes of ultrasonic treatment, high-pressure homogenization, water-based foam template, film casting, ion crosslinking, etc. The reaction conditions are mild, the process is easy to control and green and environmentally friendly, and it is easy to achieve industrial mass production; it effectively improves the comprehensive application performance of functional composite film materials, and is particularly suitable for the treatment of medium and high concentration uranium-containing wastewater. The uranium-absorbing membrane can be naturally degraded after complete desorption or disposal, and the degradation products are natural small molecules and minerals, which will not cause secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The SEM images of the attapulgite before and after the dissociation treatment of the present invention (a-before the dissociation treatment of the attapulgite, b-after the dissociation treatment of the attapulgite), the particle size distribution curve (c) and the rod crystal length distribution curve (d).

[0037] Figure 2 Optical microscope photos of the film-forming solution prepared in the present invention (left: x10 times, right: x40 times).

[0038] Figure 3 This is a digital photo of the double-crosslinked porous membrane prepared in the present invention.

[0039] Figure 4 The figure shows the changes of the double-crosslinked porous membrane prepared in the present invention when immersed in solutions with different pH values.

[0040] Figure 5 The thermogravimetric curves (a) and the differential thermogravimetric curves (b) of the pure sodium alginate membrane, the pure sodium alginate membrane after calcium crosslinking and the double crosslinked porous membrane prepared in the present invention.

[0041] Figure 6 This is a TEM image of the double-crosslinked porous membrane prepared in the present invention.

[0042] Figure 7 Microscope photos (x 10 times) of the double cross-linked porous membrane prepared in the present invention (a) and after uranium adsorption (b), digital photos after uranium adsorption (c) and FTIR spectrum (d).

[0043] Figure 8 The XPS spectra of the double cross-linked porous membrane prepared by the present invention before and after uranium adsorption are shown in Figure 1. a is the full XPS spectrum; b is the C fine spectrum; c is the O fine spectrum; d is the Ca fine spectrum; e is the U fine spectrum; and f is the P fine spectrum.

[0044] Fig. 9 The separation / enrichment performance of the double-crosslinked porous membrane prepared by the present invention for U(VI) (a, b-adsorption thermodynamic curves, b-pH boundary curve, c-adsorption kinetic curve, d-influence of solid-liquid separation on separation efficiency). DETAILED DESCRIPTION

[0045] The green construction of the double-crosslinked porous membrane of the present invention and the method for separating / enriching uranium are further described below through typical examples. First, 100g of sodium alginate and 20g of glycerol are evenly dispersed in 4.9L of deionized water under stirring conditions of 500rpm, and stirred continuously for at least 24h to obtain a uniform sodium alginate / glycerol mixed solution for standby use; separately, 80g of polyvinyl alcohol is evenly dispersed in 1.92L of deionized water under stirring conditions of 500rpm, heated to 70-80°C, and then kept warm and stirred for at least 12h to obtain a uniform polyvinyl alcohol aqueous solution for standby use. The effects of the prepared double-crosslinked porous membrane on the separation / enrichment performance of uranium-containing water with an initial concentration of 2-200ppm, contact time (15-540min), and whether solid-liquid separation is performed and other key factors are evaluated through static intermittent adsorption experiments. Specifically, the double-crosslinked porous membrane was added to a uranium-containing aqueous solution and then placed in a constant temperature shaker to reach adsorption equilibrium at 160 rpm and 25°C. The uranium concentration in the liquid phase before and after adsorption was analyzed by UV-vis spectroscopy at a maximum wavelength of 652 nm. The uranium removal rate (R, %) and adsorption amount (Q) were calculated according to formulas (1) and (2). t , mg / g).

[0046]

[0047] In the formula, C0 and C t (mg / L) are the initial and final concentrations of uranium in the uranium-containing aqueous solution, V (mL) is the volume of the uranium-containing aqueous solution, and m (mg) is the mass of the added double-crosslinked porous membrane.

[0048] Comparative Example 1

[0049] The above sodium alginate / glycerol mixed solution was used as the film-forming solution, and 10 ml of the film-forming solution was placed in a plastic tray with a diameter of 10 cm for casting. After drying, a pure sodium alginate film (marked as pure SA film) was obtained. Figure 4As shown, pure sodium alginate membrane is extremely hydrophilic and will dissolve quickly and completely once in contact with water, making it unsuitable for separation / enrichment of uranium in water.

[0050] Comparative Example 2

[0051] Take 75mL of sodium alginate / glycerol mixed solution and mix it with 25mL of water to form a film-forming solution. Take 10mL of the film-forming solution each time and place it in a plastic tray with a diameter of 10cm to form a film. Add 2.0% calcium chloride solution by mass to completely immerse the liquid film. After 4 hours, take out the above film and wash it with deionized water for 5 times to obtain a sodium alginate cross-linked film. Figure 5 As shown in Figure 2, after calcium crosslinking, the thermal stability of the film material is greatly improved. Further, the above sodium alginate crosslinked film is added to a solution with a solid-liquid ratio of 0.5 g / L at a concentration of 8*10 -4 M's uranium-containing water body, the pH value of the adjustment system was adjusted to 6.0, and after 240 minutes of oscillation reaction, the uranium adsorption amount and removal rate were calculated to be 239.6 mg / g and 62.91%, respectively.

[0052] Example 1

[0053] The construction of the double cross-linked porous membrane and the method for separating / enriching uranium therefrom comprises the following steps:

[0054] (1) 2.8g of nano-attapulgite obtained by dissociation of rod crystal bundles is uniformly dispersed in 37.2g of water to obtain a uniform suspension, 0.7g of phytic acid is added to the suspension to obtain a suspension, and the suspension is subjected to cell disruption treatment (500W, 10min) to obtain a uniform phytic acid-modified attapulgite suspension. The nano-attapulgite is a nano-powder obtained by crushing natural attapulgite ore (<100 mesh), pulping and hydration for 6h, and cyclone classification, and then subjected to ultrasonic treatment (frequency of 40kHz, power density of 100W / L for 10min) and strong drying (110°C, 5Hz); after testing, the attapulgite content in the nano-powder is 70%, and the average length of the rod crystal is about 0.97μm;

[0055] (2) 15 ml of the above phytic acid modified attapulgite suspension, 70 ml of sodium alginate / glycerol mixed aqueous solution and 15 ml of polyvinyl alcohol aqueous solution were mixed evenly and stirred at 6000 rpm for 20 min to form a uniform film-forming solution. The optical microscope photo of the film-forming solution is shown in FIG. Figure 2 ; 6 ml of the film-forming liquid was placed in a plastic tray with a diameter of 10 cm to form a film (the film thickness was 0.75 mm), and a 2.0% calcium chloride solution was added to completely immerse the film. After 4 hours, the film was taken out and washed 5 times with deionized water to obtain a double cross-linked porous membrane ( Figure 3 ).

[0056] Such as the optical microscope picture after uranium adsorption ( Figure 7 b) and digital photos ( Figure 7 c), after the double cross-linked porous membrane reacts with uranium-containing water, the membrane surface appears uniformly yellow, and the FTIR spectrum ( Figure 7 The characteristic peak of U=O in d) further confirmed that uranium was adsorbed on the double cross-linked porous membrane. -4 M, pH = 4.1, double cross-linked porous membrane was added to uranium-containing water. After shaking reaction for 4 hours, the supernatant was directly taken to test the uranium adsorption and removal rate, which were 241 mg / g and 63.29% respectively. After centrifugation (4000 rpm, 10 min), the supernatant was taken to test the uranium adsorption and removal rate, which were 240.2 mg / g and 68.08% respectively. At the same time, the effect of solid-liquid separation on uranium separation efficiency was investigated at pH = 5.9. It can be seen that the adsorption amount (339.6 and 373.2 mg / g) and removal rate (89.17 and 98.01%) of the two did not change much ( Fig. 9 d).

[0057] Example 2

[0058] The construction of the double cross-linked porous membrane and the method for separating / enriching uranium therefrom comprises the following steps:

[0059] (1) 2.8g of nano-attapulgite obtained by dissociation of rod crystal bundles is uniformly dispersed in 37.2g of water to obtain a uniform suspension with a solid content of 7%, 1.0g of phytic acid is added to the suspension to obtain a suspension, and the suspension is subjected to cell crushing treatment (200W, 20min) to obtain a uniform phytic acid-modified attapulgite suspension. Among them, the nano-attapulgite is a nano-powder obtained by crushing the natural attapulgite ore (<100 mesh), pulping and hydration for 6h and cyclone classification, and then subjected to 30Mpa high-pressure homogenization and strong drying (110℃, 5Hz); after testing, the attapulgite content in the nano-powder is 75%, and the average length of the rod crystal is about 0.90μm;

[0060] (2) 10 ml of the above-mentioned phytic acid-modified attapulgite suspension, 75 ml of the sodium alginate / glycerol mixed aqueous solution and 15 ml of the polyvinyl alcohol aqueous solution were mixed evenly, and stirred at 8000 rpm for 10 min to form a uniform film-forming liquid; 10 ml of the film-forming liquid was placed in a plastic tray with a diameter of 10 cm to cast a film (the thickness of the liquid film was 1.25 mm), and a calcium iodide solution with a mass fraction of 2.0% was added to completely immerse the liquid film. After 4 hours, the above-mentioned film was taken out and washed with deionized water for 5 times, and vacuum dried at a vacuum degree of -0.08 MPa and 40°C for 12 hours to obtain a double-crosslinked porous membrane.

[0061] The double cross-linked porous membrane was added to the uranium concentration of 2.5*10 -5 ~8*10 -4 M, pH value of 6 ± 0.1 in uranium-containing water, the effect of uranium concentration in uranium-containing water on adsorption performance was tested, and the adsorption thermodynamic curve obtained was as follows Fig. 9 Then the above double cross-linked porous membrane was added to the uranium concentration of 8*10 at a solid-liquid ratio of 0.5 g / L. -4 The adsorption and separation performance of uranium was tested at different contact times in uranium-containing water with a pH value of 6.2±0.1. The adsorption kinetic curves were as follows: Fig. 9 (c) as shown.

[0062] Example 3

[0063] The construction of the double cross-linked porous membrane and the method for separating / enriching uranium therefrom comprises the following steps:

[0064] (1) 2.8g of nano-attapulgite obtained by dissociation of rod crystal bundles is uniformly dispersed in 37.2g of water to obtain a uniform suspension with a solid content of 7%, 1.0g of phytic acid is added to the suspension to obtain a suspension, and the suspension is subjected to cell disruption treatment (500W, 20min) to obtain a uniform phytic acid-modified attapulgite suspension. Among them, the nano-attapulgite is a nano-powder obtained by crushing the natural attapulgite ore (<100 mesh), pulping and hydration for 6h and cyclone classification, and then ultrasonically treating (ultrasonizing for 5min at a frequency of 20kHz and a power density of 300W / L) and forcefully drying (110°C, 5Hz); after testing, the attapulgite content in the nano-powder is 75%, and the average length of the rod crystal is about 0.90μm;

[0065] (2) 15 ml of the above-mentioned phytic acid-modified attapulgite suspension, 75 ml of the sodium alginate / glycerol mixed aqueous solution and 10 ml of the polyvinyl alcohol aqueous solution were mixed evenly, and stirred at 8000 rpm for 10 min to form a uniform film-forming liquid; 6 ml of the film-forming liquid was placed in a plastic tray with a diameter of 10 cm to cast a film, and a calcium nitrate solution with a mass fraction of 1.0% was added to completely immerse the liquid film. After 8 hours, the above-mentioned film was taken out and washed with deionized water for 3 times, and freeze-dried at -20°C for 12 hours to obtain a double-crosslinked porous membrane.

[0066] The above double cross-linked porous membrane was added to the uranium concentration of 8*10 at a solid-liquid ratio of 0.5 g / L. -4 M in uranium-containing water, the pH value of the solution is adjusted to 4.0-9.5, and the pH boundary curve is as follows Fig. 9(b) As shown. The test point of pH = 6 was selected to verify the effect of solid-liquid separation on uranium separation efficiency. It can be seen that the adsorption amount (364.2 and 367.8 mg / g) and removal rate (95.64 and 96.57%) of the two are almost unchanged ( Fig. 9 d), and conduct comparative analysis of XPS of membrane materials before and after adsorption ( Figure 8 ).

[0067] Example 4

[0068] The construction of the double cross-linked porous membrane and the method for separating / enriching uranium therefrom comprises the following steps:

[0069] (1) 2.8g of nano-attapulgite obtained by dissociation of rod crystal bundles is uniformly dispersed in 37.2g of water to obtain a uniform suspension with a solid content of 7%, 0.7g of phytic acid is added to the suspension to obtain a suspension, and the suspension is subjected to cell disruption treatment (500W, 10min) to obtain a uniform phytic acid-modified attapulgite suspension. Among them, the nano-attapulgite is a nano-powder obtained by crushing natural attapulgite ore (<100 mesh), pulping and hydration for 6h, and cyclone classification, and then subjected to 50Mpa high-pressure homogenization and strong drying (110°C, 5Hz); after testing, the attapulgite content in the nano-powder is 70%, and the average length of the rod crystal is about 0.90μm;

[0070] (2) Wash the sapodilla fruit with water, dry it to constant weight, and crush it to obtain plant powder after passing through a 200-mesh sieve; mix 15 ml of the above-mentioned phytic acid-modified attapulgite suspension, 75 ml of a sodium alginate / glycerol mixed aqueous solution and 10 ml of a polyvinyl alcohol aqueous solution, add 0.2 g of the above-mentioned plant powder, and stir at 6000 rpm for 20 minutes to form a uniform film-forming liquid; take 10 ml of the film-forming liquid and place it in a plastic tray with a diameter of 10 cm to cast a film, and add a calcium chloride solution with a mass fraction of 2.0% to completely immerse the liquid film. After 6 hours, take out the above-mentioned film, wash it with deionized water 5 times, and vacuum dry it at a vacuum degree of -0.08 MPa and 50°C for 8 hours to obtain a double-crosslinked porous membrane.

[0071] The above double cross-linked porous membrane was added to a uranium concentration of 8*10 at a solid-liquid ratio of 0.5 g / L. -4 M's uranium-containing water body, and adjusted the pH value of the solution to 6.0. The adsorption amount and removal rate of tested uranium reached 324.88 mg / g and 85.31% respectively.

[0072] Example 5

[0073] The method for constructing a double cross-linked porous membrane comprises the following steps:

[0074] (1) 2.8 g of nano-attapulgite obtained by dissociation of rod crystal bundles was uniformly dispersed in 37.2 g of water to obtain a uniform suspension with a solid content of 7%, 1.0 g of phytic acid was added to the suspension to obtain a suspension, and the suspension was subjected to cell crushing treatment (500 W, 10 min) to obtain a uniform phytic acid-modified attapulgite suspension. Among them, the nano-attapulgite is a nano-powder obtained by crushing natural attapulgite ore (<100 mesh), pulping and hydration for 6 hours, and cyclone classification, and then subjected to 30 MPa high-pressure homogenization and strong drying (110°C, 5 Hz);

[0075] (2) Wash the fruit of soapberry with water, dry it to constant weight, and crush it to obtain plant powder after passing through a 200-mesh sieve; mix 10 ml of the above-mentioned phytic acid-modified attapulgite suspension, 75 ml of sodium alginate / glycerol mixed aqueous solution and 15 ml of polyvinyl alcohol aqueous solution, add 0.4 g of the above-mentioned plant powder, and stir at 6000 rpm for 20 minutes to form a uniform film-forming liquid. After synergistic stabilization, the foam structure in the film-forming liquid is more stable and uniform; take 10 ml of the film-forming liquid and place it in a plastic tray with a diameter of 10 cm to cast a film, and add a calcium chloride solution with a mass fraction of 1.0% to completely immerse the liquid film. After 8 hours, take out the above-mentioned film, wash it with deionized water 3 times, and vacuum dry it at a vacuum degree of -0.08 MPa and 40°C for 12 hours to obtain a double-crosslinked porous membrane.

[0076] The double-crosslinked porous membrane was added to the water body with a solid-liquid ratio of 0.5 g / L to a pH value of 6.0 and a uranium concentration of 1.2*10 -3 M (285ppm), after 240min of shaking reaction, the uranium separation efficiency was determined to be 78.15%; after the porous cross-linked membrane was removed, a new porous cross-linked membrane was added to the uranium-containing water again, and after 240min of shaking reaction, the total uranium separation efficiency was determined to be 97.31%. After the two-stage treatment, the efficient separation / enrichment of uranium in high-concentration uranium-containing water was achieved.

Claims

1. A green construction method for a double-crosslinked porous membrane, characterized in that: The following steps are involved: (1) uniformly dispersing the nano-attapulgite obtained by rod crystal bundle dissociation treatment in water to obtain a uniform suspension with a solid content of 7%, adding phytic acid in an amount of 25 to 35% by mass of the attapulgite to the suspension to obtain a suspension; and ultrasonically treating the suspension for 10 to 20 minutes to obtain a uniform phytic acid-modified attapulgite suspension; (2) The phytic acid modified attapulgite suspension, polyvinyl alcohol aqueous solution and sodium alginate / glycerol mixed aqueous solution are mixed in a volume ratio of 10-15:10-15:70-75, and stirred at 6000-8000 rpm for 10-20 min to obtain a uniform film-forming solution; the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 4%; the mass fractions of sodium alginate and glycerol in the sodium alginate / glycerol mixed aqueous solution are 2.0% and 0.4%, respectively; (3) Casting the above-mentioned film-forming liquid into a film and controlling the film thickness to be 0.75-1.25 mm, and adding a water-soluble calcium salt solution with a mass fraction of 1.0-2.0% to completely immerse the film. After 4-8 hours, take out the above-mentioned film and wash it with deionized water for 3-5 times to obtain a double-crosslinked porous membrane.

2. A green construction method for a double cross-linked porous membrane as claimed in claim 1, characterized in that: In step (1), the nano-attapulgite is obtained by crushing natural attapulgite ore, pulping and hydrating for 6 hours, and cyclone classification, and then subjecting it to ultrasonic or high-pressure homogenization and strong drying to obtain nano-powder; the attapulgite content in the nano-powder is ≥70%, and the rod crystal length is ≥0.9μm.

3. A green construction method for a double cross-linked porous membrane as claimed in claim 2, characterized in that: In step (1), the ultrasonic treatment is carried out at a frequency of 20 to 40 kHz and a power density of 100 to 300 W / L for 5 to 10 min; and the high-pressure homogenization treatment is carried out at a pressure of 30 to 50 MPa.

4. The green construction method of a double cross-linked porous membrane according to claim 1, characterized in that: In step (1), the ultrasonic treatment is performed using a cell disruptor at room temperature and a power of 200 to 500 W; the sodium alginate is a powder having a viscosity of ≥0.02 Pa.S at 10 g / L solution at 20°C; and the polyvinyl alcohol is a solid particle having a degree of alcoholysis of 87 to 89% and a viscosity of 20.5 to 24.5 CP.

5. The green construction method of a double cross-linked porous membrane according to claim 1, characterized in that: In step (2), the peel or seed shell of a saponin-rich plant is washed with water, dried to constant weight, crushed, and passed through a 200-mesh sieve to obtain plant powder, and the plant powder is added to a mixed solution of phytic acid-modified attapulgite, polyvinyl alcohol and sodium alginate / glycerol, and stirred at 6000 rpm for 20 minutes to form a uniform film-forming solution.

6. A green construction method for a double cross-linked porous membrane as claimed in claim 5, characterized in that: In step (2), the saponin-rich plant is at least one of angelica sinensis, soapberry or saponin; the added amount of the plant powder is 0.2-0.5% of the total mass of the mixed solution of phytic acid-modified attapulgite, polyvinyl alcohol and sodium alginate / glycerol.

7. A green construction method for a double cross-linked porous membrane as claimed in claim 1, characterized in that: In step (3), the water-soluble calcium salt is at least one of calcium chloride, calcium iodide, calcium dihydrogen phosphate or calcium nitrate.

8. The green construction method of a double cross-linked porous membrane according to claim 1, characterized in that: In step (3), the wet film after washing with deionized water is vacuum dried at a vacuum degree of -0.08 MPa and 40-50°C for 8-12 hours, or freeze-dried at -20°C for 12-24 hours to obtain a double cross-linked porous membrane.

9. A double-crosslinked porous membrane constructed according to any one of claims 1 to 8.

10. A method for separating / enriching uranium using a double-crosslinked porous membrane as claimed in claim 9, characterized in that: The pH value of uranium-containing water with a U(VI) concentration of 2 to 200 ppm is adjusted to 5.0 to 7.0, and 0.5 to 2.0 g / L of double-crosslinked porous membrane is added thereto. After shaking or stirring at room temperature for 60 to 240 minutes, the uranium concentration in the solution is measured, and the uranium separation efficiency is calculated according to the following formula: If the uranium separation efficiency is ≥95%, the double-crosslinked porous membrane is removed from the uranium-containing water body to achieve uranium separation / enrichment; if the uranium separation efficiency is less than 95%, the porous crosslinked membrane is removed and a new double-crosslinked porous membrane is added to the uranium-containing water body again, and the treatment is circulated until the uranium separation efficiency is ≥95%.

Citation Information

Patent Citations

  • Magnetic biological material capable of adsorbing uranium (VI) in aqueous solution and preparation method of magnetic biological material

    CN104941592A

  • Sodium alginate / carboxymethyl cellulose bifunctional microsphere adsorption material loaded with bimetal and preparation method thereof

    CN105013450B

  • Preparation method and application of sodium alginate / amino mesoporous silica gel spheres for the treatment of low-concentration uranium-containing wastewater

    CN108940225B

  • Attapulgite-doped double-crosslinking hydrogel as well as preparation method and application thereof

    CN114558558A

  • Preparation method of attapulgite-based adsorbent and application of attapulgite-based adsorbent in dye / heavy metal ion wastewater treatment

    CN114632501A